Home range and movement ecology of the woolly opossum (Caluromys derbianus) in a Neotropical rainforest of Costa Rica - Muñoz-López, Melissa; Villalobos-Chaves, David; Rojas-Valerio, Emmanuel; Rodríguez-Herrera, Bernal (Therya Notes, 2022)
Understanding animal movement is critical to elucidate how non-sessile species survive and reproduce, as well as their influence in evolutionary and ecological processes and patterns. By characterizing the spatial movements of a Neotropical mammal, we aimed to generate information regarding the home range and movement ecology of the woolly opossum, Caluromys derbianus. Fieldwork was conducted in a Neotropical Rainforest of Costa Rica where animals were captured and fitted with collar mounted radio transmitters. Data on spatial locations were then analyzed to estimate the home range and the activity areas. Mean home range and activity areas of the opossums were concentrated in small patches (< 2 ha for home range, ≤ 1.1 ha for foraging areas and < 0.5 ha for core use areas). Overall, our results contribute to the growing knowledge on the natural history of Neotropical marsupials, as well as highlights that, as expected, C. derbianus is likely a species that might meets its most critical requirements within small activity areas. So, we argue that an opportunistic and omnivorous diet, and a well conserved habitat contribute to the observed patterns of animal movement. Further efforts should focus on increasing sample size and tracking periods to better comprehend habitat and resource use patterns.